Electrohydrodynamic pumps for dielectric liquid application - Nasif, M.S. (Springer Verlag, 2019)
Operation and maintenance is a costly process in rotating equipment. Reducing this operation and maintenance is of significant economical and operational benefits in plants. Electrohydrodynamic pumping utilizes electric field to generate forces on dielectric liquids. These forces will push the liquids resulting in pumping effect. The pumping effect will be generated without the need of moving parts within the pump, hence significantly minimizing failure and required maintenance. Â© The Author(s), under exclusive licence to Springer Nature Singapore Pte Ltd. 2019.